2020
DOI: 10.1051/fopen/2020002
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: Pandemic surgery guidance

Abstract: Based on high quality surgery and scientific data, scientists and surgeons are committed to protecting patients as well as healthcare staff and hereby provide this Guidance to address the special issues circumstances related to the exponential spread of the Coronavirus disease 2019 (COVID-19) during this pandemic. As a basis, the authors used the British Intercollegiate General Surgery Guidance as well as recommendations from the USA, Asia, and Italy. The aim is to take responsibility and to provide guidance f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
27

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(86 citation statements)
references
References 89 publications
(92 reference statements)
0
59
0
27
Order By: Relevance
“…Another patient series published by Li et al from thoracic surgery department also suggests the association of higher age and chronic obstructive pulmonary disease (COPD) with disease severity (P = 0.041 and P = 0.040, respectively) and death (P = 0.015 and P = 0.038, respectively) for COVID-19 patients. In this study, five deaths (20%) among hospitalized postoperative patients were reported, leading to the conclusion that patients infected with COVID-19 in the perioperative period have a higher risk of death [7].…”
Section: Considerations For Surgical Risk Assessment Risk Stratifyinmentioning
confidence: 79%
“…Another patient series published by Li et al from thoracic surgery department also suggests the association of higher age and chronic obstructive pulmonary disease (COPD) with disease severity (P = 0.041 and P = 0.040, respectively) and death (P = 0.015 and P = 0.038, respectively) for COVID-19 patients. In this study, five deaths (20%) among hospitalized postoperative patients were reported, leading to the conclusion that patients infected with COVID-19 in the perioperative period have a higher risk of death [7].…”
Section: Considerations For Surgical Risk Assessment Risk Stratifyinmentioning
confidence: 79%
“…In addition, many aspects of surgery are considered to be aerosol generating, and therefore, health care workers are at potential risk should necessary precautions not be taken [8]. In response to this, the United Kingdom Intercollegiate guidance was published in late March and outlined recommendations for provision of surgery [9]. It concluded that laparoscopic surgery, given its potential for aerosol generation, should be considered only in selected individuals where clinical benefit exceeds the potential risk of viral transmission.…”
Section: Introductionmentioning
confidence: 99%
“…Measures such as risk assessment and serology testing of members of the teams working in the OR should be done [20]. Additionally, surgical sections should be ideally divided into two categories, a dedicated section for positive patients which only needs minimum OR and surgical staff and another section dedicated for emergency surgery and urgent oncological surgery and depending on the risk assessment, for other routine surgeries in COVID-19 negative patients [21].…”
Section: Emergency Surgery During the Covid-19 Pandemicmentioning
confidence: 99%